2011
DOI: 10.1039/c1fo10105f
|View full text |Cite
|
Sign up to set email alerts
|

Regulations applicable to plant food supplements and related products in the European Union

Abstract: This paper deals with the current regulatory and legal settings of traditional plant food supplements and herbal medicinal products in the European Union (EU). Marketing of botanicals in foods and food supplements in the EU is subject to several provisions of food law, which cover aspects of safety, production, labelling and product composition, including the use of additives and maximum levels of contaminants and residues. However, due to limited harmonization at the EU level, specific national regulations ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 1 publication
0
74
0
1
Order By: Relevance
“…With regulation of herbal products left to the agencies in each member country, at least 27 different national perspectives exist (Table 1). The second attempt in 2004 to harmonize perspectives created a category termed traditional herbal medicinal products (THMPs), providing some progress at the national level for medicinal products with traditional or historic uses (Silano et al, 2011). Authorization as a THMP requires that the product be marketed for at least 30 years, 15 of which must be in an EU member country (Silano et al, 2011).…”
Section: Regulatory Perspectives On Herbal Productsmentioning
confidence: 99%
“…With regulation of herbal products left to the agencies in each member country, at least 27 different national perspectives exist (Table 1). The second attempt in 2004 to harmonize perspectives created a category termed traditional herbal medicinal products (THMPs), providing some progress at the national level for medicinal products with traditional or historic uses (Silano et al, 2011). Authorization as a THMP requires that the product be marketed for at least 30 years, 15 of which must be in an EU member country (Silano et al, 2011).…”
Section: Regulatory Perspectives On Herbal Productsmentioning
confidence: 99%
“…The more detailed regulations on botanicals, phytotherapy, or nutritional therapy are being worked out through consultations with expert panels that can provide descriptions of regulatory hurdles for these products and practices, Good Manufacturing Practice (GMP) compliance, generally recognized as safe (GRAS) status, analytical methods and protocol validation (Silano et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, education, training and research in this area have not been accorded due attention and support: the data reported on traditional medicine are far from sufficient to meet the criteria needed to support its use worldwide (Donno et al 2013b). The lack of quality control is a major area of concern for botanicals: the quality of plant material and manufacturing processes used for phytochemicals are regulated by food laws, which lack the specificity required for botanical drugs (Silano et al 2011). It could have serious consequences: contamination, for instance, with toxins after fungal infection of raw plant material or with other ingredients has been repeatedly reported and can have potential fatal consequences (Halt 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Since acetylsalicylic acid, a synthetic derivative of salicin produced from willow bark, was first introduced in 1897 1 , natural products have become major sources for chemical compounds used as starting materials 2 . In fact, approximately 40% of current mono-molecular medicinal drugs are derived directly or indirectly from plant species and their preparations 3 . In addition, many active substances such as alkaloids, phenolic compounds and mono-, di-, tri-, and sesquiterpens with different pharmaceutical functions have been introduced from a large number of plant species 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, approximately 40% of current mono-molecular medicinal drugs are derived directly or indirectly from plant species and their preparations 3 . In addition, many active substances such as alkaloids, phenolic compounds and mono-, di-, tri-, and sesquiterpens with different pharmaceutical functions have been introduced from a large number of plant species 3 . These indicate that plants are important sources of drugs as well as phytomedicines.…”
Section: Introductionmentioning
confidence: 99%